Effects of drilled area temperatures on drilling of NFRP composites: a review - Mokhtar, Suhaily; Yusof, Nur Syahira Sofyani; Mohd Asri, Mohd Ashraff; Che Haron, Che Hassan; A. Raof, Natasha; Muhammad Khairusalleh, Nor Khairusshima; Dahnel, Aishah Najiah (The Mattingley Publishing Co., Inc., 2020)
The growth of high-performance semi-structural and structural applications made from natural resources is growing universal, due to renewable and ecological matters. Machining natural fibers reinforced polymer (NFRP) has become a challenger in the machining processes for incorporating them into the NFRP industrial production chains. The thermo-physical properties of fiber-reinforced plastics (FRPs) causes high temperatures at the tool tip when machined. The generated heat affects the process behavior as well as the machining surface quality. It causes accuracy errors when machining composites. This papers reviews the research published during drilling of natural fiber reinforced polymer composites with special reference to the effect of different cutting parameters.